Association between daily antiretroviral pill burden and treatment adherence, hospitalisation risk, and other healthcare utilisation and costs in a US medicaid population with HIV - Cohen, Calvin J (BMJ Publishing Group, 2013)
OBJECTIVES: Lower pill burden leads to improved antiretroviral therapy (ART) adherence among HIV patients. Simpler dosing regimens have not been widely explored in real-world populations. We retrospectively assessed ART adherence, all-cause hospitalisation risk and costs, and other healthcare utilisation and costs in Medicaid enrollees with HIV treated with ART as a once-daily single-tablet regimen (STR) or two or more pills per day (2+PPD). DESIGN: Patients with an HIV diagnosis from 2005 to 2009 receiving complete ART (ie, two nucleoside/nucleotide reverse transcriptase inhibitors plus a third agent) for ≥60 days as STR or 2+PPD were selected and followed until the first of (1) discontinuation of the complete ART, (2) loss of enrolment or (3) end of database. Adherence was measured using the medication possession ratio. Monthly all-cause healthcare utilisation and costs were observed from regimen initiation until follow-up end. RESULTS: Of the 7381 patients who met inclusion criteria, 1797 were treated with STR and 5584 with 2+PPD. STR patients were significantly more likely to reach 95% adherence and had fewer hospitalisations than 2+PPD patients (both p<0.01). STR patients had mean (SD) total monthly costs of $2959 ($4962); 2+PPD patients had $3544 ($5811; p<0.001). Hospital costs accounted for 53.8% and pharmacy costs accounted for 32.5% of this difference. Multivariate analyses found that STR led to a 23% reduction in hospitalisations and a 17% reduction in overall healthcare costs. ART adherence appears to be a key mechanism mediating hospitalisation risk, as patients with ≥95% adherence (regardless of regimen type) had a lower hospitalisation rate compared with <95% adherence. CONCLUSIONS: While it was expected that STR patients would have lower pharmacy costs, we also found that STR patients had fewer hospitalisations and lower hospital costs than 2+PPD patients, resulting in significantly lower total healthcare costs for STR patients.